Audience management, online turbulence and lurking in social networking services: A transactional process of stress perspective. (February 2021) - Zhang, Yun; Shi, Si; Guo, Shijun; Chen, Xiaogang; Piao, Zhirong
Highlights: We explore the antecedents and outcomes of online turbulence based on the transactional process of stress. The concept of neglected unintended audience in SNS is conceptualized. Online turbulence is a significant stressor impacting neglected unintended audience concern. Neglected unintended audience concern leads to lurking. Different types of audience management strategies have different impacts on online turbulence. Abstract: In social networking services (SNSs), users' unclear understanding of the large and invisible audience increases the chances of online turbulence, which is a key source of SNS-induced stress. This growing phenomenon has gained increasing attention in academia and industry due to the undesirable consequences for users and SNS platforms. In this study, we draw from the transactional model of stress to examine how audience management strategies impact online turbulence and lead to neglected unintended audience concern and lurking. We also investigate the role of self-monitoring as a stress inhibitor. We test our model with data collected from 301 SNS users. The results show that the four types of audience management strategies have different effects on online turbulence, which significantly impacts neglected unintended audience concern especially when users have high self-monitoring skills. We believe that this work contributes, both from scientific and practical standpoints, to the understanding of the interventions and stressful responses of online turbulence in SNSs.